2018
DOI: 10.1088/1741-2552/aae0c2
|View full text |Cite
|
Sign up to set email alerts
|

A guide towards long-term functional electrodes interfacing neuronal tissue

Abstract: Implantable electronics address therapeutical needs of patients with electrical signaling dysfunctions such as heart problems, neurological disorders or hearing impairments. While standard electronics are rigid, planar and made of hard materials, their surrounding biological tissues are soft, wet and constantly in motion. These intrinsic differences in mechanical and chemical properties cause physiological responses that constitute a fundamental challenge to create functional long-term interfaces. Using soft a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 165 publications
0
48
0
Order By: Relevance
“…For soft bioelectronics, biocompatibility and histology tests are also required to confirm the superior biointegration properties triggering lower immune response compared to state‐of‐the‐art implants. [ 31,32 ] In the case of epidural electrodes, there is no penetration by foreign material within the neural tissue. We only expected encapsulation of the implant by fibrotic tissue build‐up.…”
Section: Figurementioning
confidence: 99%
“…For soft bioelectronics, biocompatibility and histology tests are also required to confirm the superior biointegration properties triggering lower immune response compared to state‐of‐the‐art implants. [ 31,32 ] In the case of epidural electrodes, there is no penetration by foreign material within the neural tissue. We only expected encapsulation of the implant by fibrotic tissue build‐up.…”
Section: Figurementioning
confidence: 99%
“…In contrast to traditional rigid devices, they integrate well with biological tissues as a result of low mechanical mismatch and high conformability to curved biological structures. [ 1–3 ] Recently, soft and stretchable devices have been developed to interface with the central nervous system. Minev et al.…”
Section: Introductionmentioning
confidence: 99%
“…This is the main factor that limits the correct operation of a long-term implant that should be desirably active for the entire lifetime of the patient. To minimize this mechanism, four strategies can be adopted: the usage of soft materials, the implementation of surface coating to prevent biofouling, the integration of drug delivery system to control the inflammatory mechanism and the engineering of autologous cell layer to suppress the tissue response [14]. On the implant side, other issues arise in term of durability and reliability.…”
Section: Brain Challengesmentioning
confidence: 99%
“…Numerous review papers reported new findings in the part that is usually in contact with the brain, such as the electrode grid [10][11][12][13] and described physiological mechanisms underlying the implantation of these devices in the brain [14], but very few present all the fabrication methodologies that involve new materials and electronic design to allow the manufacturing of the whole system.…”
Section: Introductionmentioning
confidence: 99%